Re-Fracturing vs. CO2 Huff-n-Puff Injection in a Tight Shale Reservoir for Enhancing Gas Production - Wang, Dong; Li, Yongming; Wang, Bo; Shan, Jiquan; Dai, Libin (Frontiers in Energy Research, 2023)
Field production data indicate that the shale gas production rate decreases sharply after a few years of the first fracking. Feasible enhanced gas recovery (EGR) approaches are very necessary to be investigated. In this study, we compared re-fracturing with a huff-n-puff gas injection scheme in a shale gas reservoir for EGR. A fully compositional simulation approach coupled with a dual porosity and dual permeability model is used. The gas production performances by using different fracturing fluids (i.e., slickwater and supercritical CO2) are evaluated. The effects of huff-n-puff parameters and matrix permeability on the gas production rate and carbon sequestration are investigated. The results show that using a re-fracturing approach yields a better recovery performance than the huff-n-puff gas injection method. Re-fracturing using supercritical CO2 performs better than using slickwater because the former can create complex three-dimensional fracture networks. Huff-n-puff CO2 injection can enhance the gas recovery effectively in ultra-tight formations. In a relatively high permeable formation, viscous flow instead of adsorption-desorption isotherms becomes the primary mass transfer mechanisms, resulting in a lower gas recovery. Both the re-fracturing treatment and huff-n-puff CO2 injection are profitable from a long-term cash flowback perspective.